STRATEGI PROMOSI DALAM MENINGKATKAN JUMLAH MAHASISWA PADA PERGURUAN TINGGI - Renata, Renata; Tobari, Tobari (Graduate Program Magister Manajemen Pendidikan, 2017)
Currently, happened the competition of universities both state (PTN) and private (PTS) in Indonesia for gaining students. This study aimed at analyzing the promotional strategies, effectiveness, and inhibiting factors of promotion by using mixed method. Subjects in this study consisted of promotion team and prospective new students in PGRI University of Palembang as many as 53 people. Data were collected through interview and questionnaire, then analyzed by using data triangulation technique and regression test technique. The results showed that the promotion strategy undertaken by PGRI University of Palembang was Advertising, Personal Selling, Publicity, and Word of Mouth. Partial advertisement is the most influential variable (34,4%) whereas the least influence variable was Publicity (19,3%). Advertising Variables, Personal Selling, Publicity, and Word of Mouth simultaneously have a significant effect on the increase of the students by 65.6% while the remaining 34.4% was influenced by other variables. The inhibiting factors of promotional activities were insufficient promotional funds, lack of human resources in the field of communication science, as well as interpersonal communication that is less harmonic among employees.Â Keywords: Promotional Strategies; the Increase of the Students, PGRI Univerity of Palembang